Comparing the outcome of septoplasty and septoplasty with turbinectomy in patients with deviated nasal septum - Karodpati, Nayanna; Ingale, Mayur; Rawat, Sharad; Kuradagi, Vinayak (International Journal of Otorhinolaryngology and Head and Neck Surgery, 2019)
Background: Deviated nasal septum is a bodily disorder results in nasal obstruction. Many surgical procedures are available in correcting the disorder. The present study aimed to compare the surgical outcome of septoplasty alone and septoplasty with turbinectomy in patients with deviated nasal septum. Methods: This prospective study was done on 50 patients attending to the department of ENT of Dr. D. Y. Patil Medical College and Hospital, DPU with complaints of nasal obstruction due to inferior turbinate hypertrophy with deviated nasal septum. The severity of nasal obstruction was assessed by NOSE (nasal obstruction symptom evaluation) scale. Of them, 25 patients were managed with septoplasty alone and other 25 patients with septoplasty and turbinectomy. The outcome of both the procedures was assessed statistically by using NOSE scale. Results: Postoperative symptom improvement was seen in the both groups following surgery (p<0.05). When the NOSE scores are compared between two groups, statistically significant improvement in the symptoms (NOSE score) was seen in the group of patients treated with septoplasty and turbinectomy compared to septoplasty alone (p<0.05). Conclusions: This study re-iterates both septoplasty and concurrent turbinectomy are established mode of treatment in deviated nasal septum along with hypertrophy of inferior turbinates when the preoperative and postoperative symptoms are compared. However, the symptomatic outcomes and diagnostic nasal endoscopic findings are significantly better in patients who underwent septoplasty with concurrent resection of the inferior turbinate.